Increasing Efficiency of Dye-Sensitized Solar Cell (DSSC) Originating from Yellow Sweet Potato Extract as Dye Sensitizer: Effect of Acetic Acid, Polyethylene Glycol, and Polyvinyl Alcohol as TiO2 binders - Yulia Nadhirah; RD Kusumanto; Abu Hasan (Jurnal Kimia Sains dan Aplikasi, 2020)
This study aimed to obtain the most efficient Dye-Sensitized Solar Cell (DSSC) using yellow sweet potato extract (Ipomoea Batatas L.) as a dye sensitizer, with acetic acid, polyethyleneglycol (PEG), and polyvinylalcohol (PVA) as TiO2 binding solution. This research includes the preparation of TiO2 paste with variations: 4 g TiO2 plus 2 M acetic acid (Paste-1), 3.5 g TiO2 plus 15 mL PEG-400 (Paste-2), and 0.5 g TiO2 plus 0.75 mL. PVA (Paste-3). Anthocyanin dye from yellow sweet potato was prepared and used to soak the TiO2 photoelectrode for 24 hours. UV-vis and FTIR spectra of dye solution from yellow sweet potato extract showed anthocyanin content at a maximum wavelength of 283 nm and were strengthened by the appearance of hydroxyl groups in the infrared spectra. The highest DSSC efficiency of 0.302% was obtained from PVA as a TiO2 binder, with an electric current of 0.0204 mA and an electric voltage of 338 mv.